Price spillovers in Norway: Less prevalent after the 1980s - Kristine Aunvåg Matsen (Norges Bank, 2023)
This Staff Memo considers some of the available evidence on relative price shocks as a driver of Norwegian inflation dynamics in high- versus low-inflation regimes. The results suggest that relative price shocks have largely been transient over the past two-three decades. However, this has been a period of low and stable inflation. Evidence from the 1980s suggest that relative price shocks had greater passthrough to other prices, and thus core inflation, in a high inflation regime.
hdl:11250/3073129
Keywords: 330; Inflation; relative prices